Constraints and Determinants in the Adoption of Mechanisation in Rice Cultivation - F. Mary Regina,; P. Shaji James,; P. Ahamed, (Journal of Agricultural Extension Management, 2013)
In an effort to sustain rice cultivation in Kerala, there has been a major thrust on farm mechanisation by the State as well as the local self governments especially in Palakkad and Thrissur districts of Kerala. This study was taken up to identify the major constraints and determinants in the adoption of mechanisation in rice cultivation. Socio-economic constraints include small holding si-::,e, lack of unity among the farmers to adopt group mechanisation followed by the technological constraint i.e, non-availability of skilled personnel for operation. Important determinants in the adoption of rice mechanisation include availability of machines, availability of trained operators. Initiative and responsibility in upkeep of machinery and the unity of farmers. There is a need for awareness programs apart from focus on a group mechanisation strategy where individual holdings are too small to own machines.